2012
DOI: 10.1002/anie.201204007
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐free Catalytic Olefin Hydrogenation: Low‐Temperature H2 Activation by Frustrated Lewis Pairs

Abstract: The hydrogenation of double bonds is one of the most fundamental transformations [1] in organic chemistry, and has numerous applications in the commodity chemical, agrochemical, pharmaceutical, polymer, and food industries. [2] Despite significant advances in the last 100 years, efforts to improve metal-based technologies for hydrogenation are still the focus of current research. [3] In parallel to these continuing efforts, metal-free strategies for effecting reductions have also been pursued. While organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
127
0
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 248 publications
(136 citation statements)
references
References 75 publications
3
127
0
6
Order By: Relevance
“…[2] Grimme,P aradies,a nd co-workers demonstrated that hydrogenation reactions of EDG-substituted C=Cd ouble bonds proceed through initial protonation, and that substrates with nucleophilicity parameters 1 < N < 5o n the Mayr reactivity scale [3] can be hydrogenated by the use of ac ombination of tris(1-naphthyl)phosphane (C 10 H 7 ) 3 Pa nd B(C 6 F 5 ) 3 as the catalyst. [4] On the other hand, hydrogenation reactions of nitroalkenes and acrylates were not catalyzed by FLPs derived from B(C 6 F 5 ) 3 (1a), but proceeded smoothly when aL ewis pair derived from the less acidic borane B(2,6-F 2 C 6 H 3 ) 3 (1c) was employed (Scheme 2). [5] Analogously,A lcarazo and coworkers explored the catalytic hydrogenation of electronpoor alkenes with FLPs derived from differently fluorinated triaryl boranes and 1,4-diazabicyclo[2.2.2]octane (DABCO) and found that only B(2,4,6-F 3 C 6 H 2 ) 3 (1b)and B(2,6-F 2 C 6 H 3 ) 3 (1c)s howed catalytic activity.…”
mentioning
confidence: 99%
“…[2] Grimme,P aradies,a nd co-workers demonstrated that hydrogenation reactions of EDG-substituted C=Cd ouble bonds proceed through initial protonation, and that substrates with nucleophilicity parameters 1 < N < 5o n the Mayr reactivity scale [3] can be hydrogenated by the use of ac ombination of tris(1-naphthyl)phosphane (C 10 H 7 ) 3 Pa nd B(C 6 F 5 ) 3 as the catalyst. [4] On the other hand, hydrogenation reactions of nitroalkenes and acrylates were not catalyzed by FLPs derived from B(C 6 F 5 ) 3 (1a), but proceeded smoothly when aL ewis pair derived from the less acidic borane B(2,6-F 2 C 6 H 3 ) 3 (1c) was employed (Scheme 2). [5] Analogously,A lcarazo and coworkers explored the catalytic hydrogenation of electronpoor alkenes with FLPs derived from differently fluorinated triaryl boranes and 1,4-diazabicyclo[2.2.2]octane (DABCO) and found that only B(2,4,6-F 3 C 6 H 2 ) 3 (1b)and B(2,6-F 2 C 6 H 3 ) 3 (1c)s howed catalytic activity.…”
mentioning
confidence: 99%
“…[55] Paradies and Grimme reported that combinations of 27, BCF, and H 2 in methylene chloride had the same NMR fingerprints of the constituents at room temperature, suggesting, at first blush, the inactivity of the system. When these mixtures were cooled to À80 8C, the formation of phosphonium borate salt [(C 6 F 5 )Ph 2 PH] [HB(C 6 F 5 ) 3 ] was observed, while raising the temperature, the salt readily releases H 2 to restore the initial mixture.…”
Section: Reactions With Hmentioning
confidence: 97%
“…[3] Diese Systeme sind auf Reduktionen, d. h. übergangsmetall-freie Hydrierungen, einer Vielzahl an Substraten anwendbar. [4][5][6][7][8][9] Wirh atten jüngst gezeigt, dass dasselbe Gesamtergebnis durch Einsatz von Cyclohexa-1,4-dienen als Diwasserstoffsurrogate erreicht wird (Schema 1, oben). [10] B(C 6 F 5 ) 3 ist in der Lage,e in Hydrid von geeignet substituierten Cyclohexa-1,4-dienen zu abstrahieren.…”
unclassified
“…[14,15] Die Gegenwart von Carbeniumionen in verschiedenen Schritten dieses Prozesses lçst jedoch hçchst-wahrscheinlich kationische Oligomerisierungen beider Reaktionspartner aus.E sm uss erwähnt werden, dass Stephan und Mitarbeiter vor einiger Zeit über ein Beispiel einer B-(C 6 F 5 ) 3 -katalysierten Alkenhydrierung berichteten, in der Et 2 Oa ls Lewis-basische Komponente zugesetzt werden muss. [8,9,16,17] Dasselbe Labor arbeitete auch eine durch das Lewis-acide Phosphoniumion [(C 6 F 5 ) 3 PF] + katalysierte Tr ansferhydrierung von Alkenen aus,inder das Hydrid sowie das Proton in einer vorgelagerten dehydrierenden Si-O-oder Si-N-Kupplung generiert werden. [18] Wirs tellen hier eine Tr ansferhydrierung von 1,1-disubstituierten Alkenen vor,die nur mit B(C 6 F 5 ) 3 katalysiert wird.…”
unclassified
See 1 more Smart Citation